Acute Lymphoblastic Leukemia With Surface Light Chain Expression - Bapat, Kalyani; Mansukhani, Dia; Khodaiji, Shanaz; Almel, Sachin (Annals of Pathology and Laboratory Medicine, 2023)
Acute Lymphoblastic leukemias (ALL) are a heterogeneous group of neoplasms which can either be having precursor B cell immunophenotype or mature B cell immunophenotype. Surface immunoglobulin light chain restriction is usually a feature of mature B cell neoplasms. A precursor B cell lymphoblastic leukemia (pre-B-ALL) with surface immunoglobulin light chain expression is a rare immunophenotype . We report a case of a 4 year old female with L1 type of blast morphology yet showing surface light chain restriction. Recognizing this rare immunophenotype and arriving at a correct diagnosis has therapeutic implications as treatment regimens differ for precursor B ALL as compared to mature B cell neoplasms.